Some physical characteristics of thermally modified oriental-beech wood - Baysal, Ergun; Kart, Saban; Toker, Hilmi; Degirmentepe, Selim (Maderas. Ciencia y Tecnología, 2025)
Heat treatment of Oriental-beech (Fagus orientalis) wood was carried out by hot air in an oven for 2, 4, and 8 h at 140, 170, and 200°C. After heat treatment, some physical characteristics such as surface roughness, color, glossiness, and mass loss of Oriental-beech wood specimens were measured. Our results showed that heat treatment caused decrease in surface roughness, glossiness, and mass loss values of Oriental-beech (Fagus orientalis) wood specimens. The decrease in lightness at all temperatures indicates that the specimens become darker with the treatment time. While, a* coordinate (red component) decreased as temperature increased, b* coordinate (yellow component) initially increased at 140°C and then decreased at 170°C and 200°C.